Association of Serum Iron Indices with Insulin Resistance Index in Euglycaemic Offspring’s of Diabetic and Non Diabetic Parents: A Case-control Study - MV Shobha; A Jagadamba; K Prabhakar; KN Shashidhar (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Altered iron metabolism may be a risk factor for various diseases. There are studies showing that altered iron metabolism is frequently found in type 2 diabetes mellitus patients, but there is lacunae of literature in offspring’s of diabetic parents. Aim: To compare serum iron indices in euglycaemic offsprings of diabetic and non diabetic parents and also to correlate serum iron indices with HOMA-IR. Materials and Methods: This was a case-control study conducted in RL Jalappa Hospital and Research Centre, Kolar, Karnataka, India, from February 2019 to January 2020. Total 80 euglycaemic healthy individuals were recruited. Out of 80 subjects 40 were cases and 40 were controls. Offspring of non diabetic parents as control group and offspring of diabetic parents as a case group were included in the study. Anthropometric measurements like weight, height was measured and Body Mass Index (BMI) was calculated. Laboratory parameters like complete haemogram, Fasting Blood Sugar (FBS), serum iron markers like serum iron, serum ferritin, serum Total Iron Binding Capacity (TIBC), serum insulin and high sensitive C-reactive protein were analysed and compared between cases and controls. Homeostasis Model Assessment-estimated Insulin Resistance (HOMA-IR) was calculated. Results: Mean age of cases was 34.65±3.06 years and controls was 35.75±3.43 years respectively. Out of total 24 were females and 56 were males. Serum iron markers like serum iron and serum ferritin was significantly increased and serum TIBC was significantly decreased among euglycaemic offspring’s of diabetic parents compared to offspring’s of non diabetic parents. Serum ferritin (r-value=0.389, p-value=0.007) and serum iron (r-value=0.483, p-value=0.001), showed positive correlation with HOMA-IR among euglycaemic offspring’s of diabetic parents. On multiple regression analysis, in model 1 (HOMA-IR as dependent variable and serum ferritin, serum iron and serum TIBC as independent variable) serum iron emerged as a significant predictor of insulin resistance, whereas after adding confounding variables like BMI, high sensitivity C-Reactive Protein (hsCRP), lipid profile with serum iron markers in model 2, serum iron emerged as independent predictor of insulin resistance though regression equations was not statistically significant. Conclusion: Offsprings of diabetic parents showed iron overload and insulin resistance which predisposes them to develop T2DM and serum iron can be used as one of the marker of insulin resistance among offspring of diabetic parents along with other parameters.